Aerobic and anaerobic abilities and their relationship to muscle fatigue index and skill performance for junior footballers - Khader, Rizgar (Humanities Journal of University of Zakho, 2022)
The study aims to assess the aerobic and anaerobic capabilities of football juniors and to identify the effect of aerobic capacity on the fatigue index and skill performance of junior football and also to identify the effect of anaerobic ability on the fatigue index and skill performance of junior football, The research community was chosen from the juniors of the Koya Sports Club in football, while the research sample was chosen in a deliberate way, as they represent (77.77%) of the juniors of the Koya Sports Club in football, Four players were disqualified for their participation in an exploratory experiment, The descriptive method was used, He also used a number of tools and means to collect data, Several exploratory experiments were conducted to ensure the correctness of the performance of the tests, The researcher also used the statistical package (SPSS) to extract the results, Statistical means (skew coefficient, simple correlation coefficient, mean, standard deviation, and percentage) were used, After obtaining the results, they were discussed in a scientific manner supported by the sources to achieve the objectives of the research, Through these results, the researcher reached a set of conclusions, Including the existence of a significant correlation between aerobic capacity, muscle fatigue index, and handling skill among junior footballers, And also between anaerobic ability, muscle fatigue index, and scoring skill among junior footballers, And the absence of a significant correlation between aerobic ability and skills (rolling, damping and scoring) among junior footballers, And between anaerobic ability and skills (rolling, damping and handling) among junior footballers.